Mitochondrial Targeting Therapeutics: Promising Role of Natural Products in Non-alcoholic Fatty Liver Disease - Xu, Jingqi; Shen, Jiayan; Yuan, Ruolan; Jia, Bona; Zhang, Yiwen; Wang, Sijian; Zhang, Yi; Liu, Mengyang; Wang, Tao (Frontiers in Pharmacology, 2021)
Non-alcoholic fatty liver disease (NAFLD) has become one of the most common chronic liver diseases worldwide, and its prevalence is still growing rapidly. However, the efficient therapies for this liver disease are still limited. Mitochondrial dysfunction has been proved closely associated with NAFLD. The mitochondrial injury caused oxygen species (ROS) production and oxidative stress can aggravate the hepatic lipid accumulation, inflammation and fibrosis. which contribute to the pathogenesis and progression of NAFLD. Therefore, pharmacological therapies that targeting mitochondria could be a promising way for the NAFLD intervention. Recently, natural products targeting mitochondria have been extensively studied and have shown promising pharmacological activity. In this review, the recent research progress on therapeutic effects of natural products derived compounds that targeting mitochondria and combating NAFLD was summarized, aiming to provide new potential therapeutic lead compounds and reference for the innovative drug development and clinical treatment for the NAFLD.